ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PT. PAKOAKUINA OLEH PT. ASTRA OTOPARTS, TBK - Dellas Devida Yunisaputri Sri Ulina Tari (Jurnal Ilmiah Mahasiswa FEB, 2016)
Acquisition is one type of business combination, where the acquired company’s system and ownership, wholly or partially, go to the acquiring company. However, after the acquisition both companies continue their business. The purpose of this research is to measure and analyze the financial performance of PT Pakoakuina before and after its acquisition by PT Astra Otoparts, Tbk. the financial performance is measured using liquidity ratios (current ratio, quick ratio), solvency ratios (total debt to equity ratio, total debt to asset ratio), profitability ratios (net profit margin, return on equity, return on asset), activity ratios (total assets turn over) and market ratios (earning per share). The overall values of these ratios decreased after the acquisition. Paired Sample t-Test was used to find any difference on the financial performance before and after the acquisition. The results show that there is no significant differences on current ratio, quick ratio, net profit margin, return on equity, return on asset, total assets turn over, and earning per share before and after the acquisition. However, there are significant differences on total debt to equity ratio and total debt to asset ratio before and after the acquisition by PT Astra Otoparts, Tbk.Keywords: Acquisition, Financial ratio, and Paired Sample t-Test